Mimoune - Ballester, Gonzalo (Spain)
Illegal immigration is not only a problem to the host society; for immigrants the social uprooting comes with the family division. This documentary was born of the desire to put together, even if it was only through a camera, a family that since long ago wishes to be reunited.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films